2008
DOI: 10.1136/gut.2008.171116
|View full text |Cite
|
Sign up to set email alerts
|

Stem and progenitor cells for liver repopulation: can we standardise the process from bench to bedside?

Abstract: There has been recent progress in the isolation and characterisation of stem/progenitor cells that may differentiate towards the hepatic lineage. This has raised expectations that therapy of genetic or acquired liver disease might be possible by transplanting stem/progenitor cells or their liver-committed progeny. However, it is currently impossible to determine from the many documented studies which of the stem/progenitor cell populations are the best for therapy of a given disease. This is largely because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 67 publications
1
96
0
7
Order By: Relevance
“…Alcohol also affects the expression of adhesion molecules [135] , which may be a concern when using adherent cell types due to possible cell detachment. Additional concerns arise from the possibility of modified ex vivo function of some primary cells, including hepatocytes, stellate cells and their precursors, due to limited ex vivo environment compared to in vivo conditions [136][137][138] . From a technical point, the acute alcohol exposure of cells in vitro may be hampered by alcohol evaporation.…”
Section: In Vitro Aaa Modelmentioning
confidence: 99%
“…Alcohol also affects the expression of adhesion molecules [135] , which may be a concern when using adherent cell types due to possible cell detachment. Additional concerns arise from the possibility of modified ex vivo function of some primary cells, including hepatocytes, stellate cells and their precursors, due to limited ex vivo environment compared to in vivo conditions [136][137][138] . From a technical point, the acute alcohol exposure of cells in vitro may be hampered by alcohol evaporation.…”
Section: In Vitro Aaa Modelmentioning
confidence: 99%
“…Treatment of acute liver failure caused by partial hepatectomy [35] or a single CCl4 injection [36] has suggested that bone marrow MSC undergo myofibroblast differentiation contributing therefore to progression of fibrosis. Taken together, an overview of the results obtained by several different groups indicates that correct evaluation of liver parameters in preclinical liver disease models is needed and that results obtained may simply reflect in inherent variability of the experimental animals, as already previously noted [37] . In the experiment where data are collected before and after the treatment, the individual variability of serum parameters is evident, though macroscopically the disease is present in all animals.…”
Section: Figurementioning
confidence: 94%
“…However, it is currently impossible to determine from the many documented studies which of the stem/progenitor cell populations are the best for therapy of a given disease. 39 The liver, in the healthy adult, such as many other organs maintains a perfect cells gain and loss balance. There are three levels of cells that can respond to loss of hepatocytes:…”
Section: Overview Of Liver Alterationsmentioning
confidence: 99%